When the Sun Shines it's Almost Heaven - V. Supino (Язык и текст, 2021)
The article describes Fyodor Mikhailovich Dostoevsky's visit to Italy. Fyodor Mikhailovich was in Italy three times. For the first time in 1862, after visiting Paris and London, in his winter Notes on summer impressions, he fought both for the mores, especially the bourgeois ones, and for the inhabitants, whom he despises to the maximum and ridicules them. Dostoevsky was not an ordinary tourist: he was interested in the history of the country, Italian politics, risorgimental movements, the struggle for unification. He was a big fan of Garibaldi. He visited Italy for the second time with his great love Apollinaria Suslova in 1863. The third time he arrived in Italy in 1868, after marrying Anna in 1867, they decided to move to Europe in order to avoid the imprisonment of Dostoevsky F. M. for debts, and also to protect Anna from the oppression that the family had caused her to suffer. Also Dostoevsky F. M. was strongly impressed by painting and in his works you can notice the presence of art in general and in particular Raphael.